Oral frailty and activities of daily living among community-dwelling older adults: the indirect association of nutritional status - Wei Jiang; Yaoqun Zhou; Xiaotong Feng; Chengyang Xie; Ronghua Fang; Xiaofeng Xie (Frontiers in Public Health, 2026)
Background The acceleration of global population aging has made functional decline and increased care demand among older adults a major public health concern. Activities of daily living (ADL) are key indicators of basic function in older adults. Therefore, identifying factors associated with ADL among older people is critically important. This study aimed to examine the relationship between oral frailty and ADL among community-dwelling older adults in Chengdu, China, and to explore the statistical indirect association involving nutritional status. Methods This multicenter cross-sectional study (January to March 2024) enrolled adults aged ≥60 years through convenience sampling from 12 community health service centers in Chengdu, China. Oral frailty, nutritional status, and ADL were assessed using the Oral Frailty Index-8 (OFI-8), Mini Nutritional Assessment-Short Form (MNA-SF), and Barthel Index (BI), respectively. Associations were examined using Spearman’s correlation analysis, multiple linear regression, and upper-censored Tobit regression. The statistical indirect association involving nutritional status was estimated using bootstrapping. Results Among the 401 participants, 78 (19.5%) had impaired ADL, 164 (40.9%) had oral frailty, and 48 (12.0%) were at risk of malnutrition. Oral frailty was weakly negatively correlated with nutritional status (rs = −0.157, p < 0.01) and ADL (rs = −0.294, p < 0.01); nutritional status was weakly positively correlated with ADL (rs = 0.119, p < 0.01). After covariate adjustment, oral frailty was negatively associated with nutritional status (B = −0.116, p = 0.001), and nutritional status was positively associated with ADL (B = 3.129, p = 0.006). The direct association between oral frailty and ADL remained negative and significant after nutritional status was included (B = −2.261, p = 0.012). The indirect association through nutritional status was significant but small in magnitude (B = −0.363, 95% bootstrap: −0.798 - -0.044). Conclusion Among community-dwelling older adults recruited in Chengdu, China, greater oral frailty was associated with poorer nutritional status and lower ADL. Nutritional status showed a statistically significant but small indirect association between oral frailty and ADL. Given the cross-sectional design, the temporal sequence and causal relationships among these factors cannot be established. Prospective studies are needed to confirm these findings.